Nitrogen Post Modification of PtRu/Carbon Catalysts for Improved Methanol Oxidation Reaction Performance in Alkaline Media. Issue 8 (6th June 2015) - Wood, Kevin N.; Dameron, Arrelaine A.; Joghee, Prabhuram; Bender, Guido; O'Hayre, Ryan; Pylypenko, Svitlana
Abstract : This work compares the methanol oxidation performance and stability of a commercial PtRu/Carbon catalyst post modified with nitrogen against an unmodified counterpart in alkaline media. Commercially available Hi-Spec JM10000 (PtRu) was modified with nitrogen via ion implantation in order to modify those areas not shielded by the pre-existing catalyst. The effects of this process on the structure and chemical composition of the catalyst and carbon support were explored using X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM), while the electrochemical performance and stability of the catalyst were then investigated using rotating disk electrode experiments. Compared to the unmodified catalyst, the N-modified sample had a higher initial electrochemical surface area, likely resulting from the ablation and redeposition of PtRu during the implantation process. Accelerated degradation test (ADT) results showed that nitrogen modification reduced surface area loss, helped to retain ruthenium, and improved methanol oxidation performance by nearly double. The benefits of nitrogen doping to improve state-of-the-art electrocatalysts combined with advantages of alkaline media improve the viability of widespread commercialization of direct methanol fuel cells.